Experience with digital mammography - G. P. Korzhenkova; B. I. Dolgushin (Опухоли женской репродуктивной системы)
The use of digital techniques in mammography has become a last step for completing the process of digitization in diagnostic imaging. It is assumed that such a spatial decision will be required for digital mammography, as well as for high-resolution intensifying screen-film systems used in conventional mammography and that the digital techniques will be limited by the digitizer pixel size on detecting minor structures, such as microcalcifications. The introduction of digital technologies in mammography involves a tight control over an image and assures its high quality.